Botanical collections as an opportunity to explore nature through the time: An untargeted metabolomic study in historical and modern Nicotiana leaves. (May 2023) - Badillo-Sanchez, Diego; Serrano Ruber, Maria; Davies-Barrett, Anna M.; Jones, Donald JL.; Inskip, Sarah
Abstract: Living and dried specimens in botanical collections play an important role in society for scientific purposes, offering the opportunity to obtain both macroscopic and molecular information for individual plants, ecosystems, and environmental studies. Untargeted metabolomics is an analytical approach that permits the simultaneous study of multiple small molecules present in an organism, which allows us to statistically compare different conditions of interest. Metabolomic approaches have been used on living specimens in botanical collections, but until now, not on historical dried material. Using the Nicotiana genus herbaceous plant (tobacco) as a case study, we propose an untargeted metabolomic study to evaluate the potential of dried historical specimens as a source of metabolomic information for the past. The metabolomic profile from polar and less-polar/apolar aqueous extracts of four modern handmade tobacco cigars (split into wrapper, binder, and filler leaves), and a set of eight late-19th to early-20th century tobacco specimens (seven tobacco leaves and one snuff powder) from the collection of the Royal Botanical Gardens at Kew (London, UK) were analysed by liquid chromatography coupled to high resolution mass spectrometry. Results showed that a wide range of polar and less-polar/apolar molecules are preserved in dried botanical material providing information optimal for metabolomic studies. The metabolomic profiles of historical dried samples were distinct enough to classify as Nicotiana tabacum or Nicotiana rustica, and showed differences based on geographic provenance or transformation/processing. Statistical models based on the molecular data from the historical material permitted us to validate the labelling of the historical collection, which identified one possible mislabelled specimen and offered some clues as to the species of one unknown Nicotiana sample. Finally, metabolomic differences in profiles between Nicotiana tabacum and modern cigars showed that both share a large proportion of their metabolomic profile, where molecular differences could be possibly associated with both location of growth and/or anthropogenic transformation of the plant in the last two centuries. This study demonstrates that dry botanical collections are a feasible source of information, and, if applied to a large set of individuals, conclusions may be drawn about the possible evolution and anthropogenic modification over time in plant material. The results are significant for disciplines interested in the history of plants, such as botany, history and archaeology. Highlights: Metabolomics assays on dry botanical collections provide new molecular data from vegetal samples. Small molecules are preserved in dry botanical material stored in botanical collections. Untargeted metabolomics assays in dry botanical material offer new insights to archaeological sciences. Profile of metabolites preserved in dry botanical material permits differention between species, locations and products.